Methods to Evaluate Uptake of Engineered Nanomaterials by the Alimentary Tract. Issue 4 (July 2014) - Alger, Heather; Momcilovic, Dragan; Carlander, David; Duncan, Timothy V.
Abstract This article is one of a series of 4 that report on a task of the NanoRelease Food Additive project of the International Life Science Institute Center for Risk Science Innovation and Application to identify, evaluate, and develop methods that are needed to confidently detect, characterize, and quantify intentionally produced engineered nanomaterials (ENMs) released from food along the alimentary tract. This particular article focuses on the problem of detecting and characterizing ENMs in the various compartments of the alimentary tract after they have been ingested from dietary sources. An in depth analysis of the literature related to oral toxicity of ENMs is presented, paying particular attention to analytical methodology and sample preparation. The review includes a discussion of model systems that can be used to study oral uptake of ENMs in the absence of human toxicological data or other live‐animal studies. The strengths and weaknesses of various analytical and sample preparation techniques are discussed. The article concludes with a summary of findings and a discussion of potential knowledge gaps and targets for method development in this area.